Financial burden of catastrophic health expenditure on households with chronic diseases: financial ratio analysis - Hyunwoo Jung; Young Dae Kwon; Jin-Won Noh (BMC, 2022)
Abstract Background The financial status of households is vulnerable to chronic diseases which entail high medical expenses and income loss. Financial strain can be assessed by four indicators: a household surplus indicator, the liquid asset/debt ratio, a solvency indicator, and a liquidity indicator. We investigated the association between catastrophic health expenditure (CHE) and financial ratio indicators in households with chronic diseases in South Korea. Methods This study applied thresholds to the financial ratios to determine the financial strain. We conducted multiple logistic regression analyses to determine whether CHE is associated with financial strain. Furthermore, we analyzed the relationship between CHE and basic financial indicators, absolute finance size, using multiple linear regression. Results When CHE occurred, all financial ratio indicators deteriorated. However, this was not due to decreases in the absolute size of wealth and income, but rather the relative balance between finances. In particular, the loss of liquid assets was a major factor in the deterioration. In addition, all types of labor-related income deteriorated; only private transfer income increased. Conclusions This study revealed that CHE in households with chronic diseases negatively impacts household finances. It was found that financial coping strategies are only resource consuming.